Early detection of orange spotting disease in oil palm using red edge parameters - Golhani, Kamlesh (2018)
Viroids are single-stranded, low molecular weight, circular RNA between 246 and 401 nucleotides that lacks a protective protein coat. Viroids have only been found in the plants. Coconut cadang-cadang viroid (CCCVd; Genus Cocadviroid, Family Pospiviroidae) is one of the known species of viroids that has been reported to cause Orange Spotting (OS) disease in the oil palm (Elaeis guineensis Jacq.; Arecaceae). OS disease is an emerging oil palm disease in Malaysia. Variants of CCCVd have been reported in both symptomatic and asymptomatic oil palm. Currently, there is no direct control measure reported that can be recommended to control OS disease. Replacement of the infected plants is the only measure to reduce losses. Molecular marker techniques are used to detect CCCVd-infected plants. But these techniques are destructive and typically take a longer time in molecular analysis and sequence characterisation. Therefore, for early disease detection, visible-near infrared spectroscopy was employed for the first time at the leaf scale to screen oil palm seedlings using a hand-held spectroradiometer. Glasshouse experiment was conducted on three-month-old inoculated and healthy oil palm seedlings for a duration of four months in two different years, 2015 and 2017. In this research, oil palm seedlings were inoculated with a CCCVd oil palm variant (OP246), and an ASD spectroradiometer was employed to measure reflectance from inoculated and control seedling. In particular, the red edge region (680-780 nm), which has been frequently shown to indicate plant stress, was investigated for selection of red edge wavebands, red edge indices, and development of the Orange Spotting Disease Index (OSDI) using red edge parameters. Firstly, using a standard foreoptic with a 25° Field of View (FOV), two red edge wavebands (i.e. 680 nm and 754 nm) were identified. Their reflectance sensitivity was also examined. Secondly, using a contact probe, two other red edge wavebands (i.e., 700 nm and 768 nm) and a red edge index (i.e., Enhanced Vegetation Index 2) were identified. Finally, a simple ratio, i.e. the sum of the first derivative spectra of right side – Red Edge Point (REP) to the sum of the first derivative spectra of left side – REP of the red edge region, was developed as an OSDI. The OSDI values between experiment batch of 2015 and 2017 demonstrated a strong correlation (r = 0.96). The OSDI is a first spectral index developed for early detection of OS disease at the leaf scale and can be tested at canopy scale in the future. This study has proved that OS disease can be detected at an early stage using a hand-held spectroradiometer.